Pathological Review of Clinical Autopsy in The Perspective of Health Law in Indonesia - Muhammad Yoga Dwi Anggara Sopiyan; Fahmi Irsan Nasution; Hendri meirialdi (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Clinical autopsy is an important procedure in the medical world to determine the exact cause of death and evaluate the quality of medical services. In Indonesia, its implementation is still limited due to various legal, social, and ethical obstacles. This article discusses the position of clinical autopsy from the perspective of pathology and medicolegal forensics and examines the relevant legal framework for health in Indonesia. This study aims to encourage the implementation of autopsy legally, professionally, and ethically through a multidisciplinary approach. In conclusion, regulatory reform and enhanced education are needed to support the implementation of clinical autopsies that are legally valid and beneficial for both the medical and legal fields.